Proposal of a system of activities to enhance motivation towards the teaching and learning process of the speaking ability in “Rafael Santana Castillo” Elementary School - Suárez Pérez, Nirely (Universidad de Ciencias Pedagógicas "Félix Varela Morales", 2013)
The teaching of foreign languages has been widely spread all over the world and English has become a priority because of its importance as an international language. Learning of a foreign language is considered difficult or, in some occasions, boring by most learners. In this content, motivation is essential to get an effective learning. Motivation should be highlighted for the activity in the foreign language, since it is a decisive factor that guarantees the success in learning. Motivation is also a crucial aspect in all teachings, but especially in the Elementary School Level. The research is derived from the necessity that the students from 5th grade at ´´Rafael Santana Castillo ´´Elementary School in Placetas have shown in their motivational sphere towards the teaching and learning process of speaking in English which has brought about limitations related to the development of the speaking ability. The initial diagnostic allowed to determine the students ‘strengths and weaknesses through the use of different methods from the empirical and theoretical levels. A system of activities to enhance the students ‘motivation towards the teaching and learning process of speaking is proposed; it takes into account the students´ level, motivations, interests and needs. It is also characterized by being interesting, motivating, profitable and based on real and simple situations according to the students' age .Besides, it favors the students´ collective and systematic work,their enjoyment , active participation and their exchange of ideas, feelings, experiences and opinions as well as their security and confidence during communication which contribute to develop values as solidarity ,responsibility, respect for their peers affection, politeness, kindness and modesty in these relationships. The proposal was positively evaluated by the specialists’ criterion who considered it pertinent to enhance motivation as well as to contribute to the development of the speaking ability in the students of this grade

La enseñanza de idiomas extranjeros ha sido ampliamente expandida alrededor del mundo y el inglés se ha convertido en una prioridad debido a su importancia como idioma internacional. El aprendizaje de un idioma extranjero es considerado difícil, y en ocasiones aburrido por muchos aprendices. En este contexto la motivación es esencial para alcanzar un aprendizaje efectivo. La motivación debe ser sobresaltada por la actividad en el idioma extranjero ya que es un motor impulsivo y un factor decisivo el cual garantiza el éxito en el aprendizaje. La motivación es además un aspecto crucial en todas las enseñanzas, pero especialmente en el Nivel Primario. La presente investigación se deriva de la necesidad que presentan los estudiantes de 5to grado de la escuela primaria SI Rafael Santana Castillo, del municipio de Placetas con el fin de lograr la motivación de estos para resolver sus limitaciones relacionadas con el desarrollo de las habilidades orales en inglés. El diagnóstico inicial permitió determinar las fortalezas y debilidades de los estudiantes a partir de la utilización de varios métodos de investigación, del nivel teórico, empírico, así como del matemático. Para contribuir a transformar la variable dependiente motivación hacia el proceso de enseñanza aprendizaje de las habilidades orales en inglés se propone como aporte un sistema de actividades variadas de acuerdo a las necesidades, motivaciones, los intereses y el nivel de los alumnos. Este se caracteriza por ser novedoso, interesante, motivante, provechoso y basado en situaciones reales y sencillas propias de su edad. Además propicia el trabajo colectivo y sistemático, el disfrute, la participación activa y creadora, el intercambio de ideas ,sentimientos, experiencias y opiniones así como la seguridad y confianza durante la comunicación desarrollando en ellos valores esenciales como: la responsabilidad, solidaridad, respeto por los compañeros mostrando afecto ,cortesía, amabilidad y modestia en estas relaciones. Finalmente este fue evaluado positivamente por el criterio de especialistas lo que lo consideraron pertinente para lograr la motivación así como para contribuir al desarrollo de la habilidad oral en los estudiantes de este grado.
Keywords: Educación Primaria; Expresión Oral; Inglés; Enseñanza; English; Enseñanza de Idiomas; Lenguas Extranjeras